HAEMATOLOGICAL INDICES IN OSTEOFLUOROSIS IN A TINNY VILLAGE - K. MYTHILI; DEVI, D K. SOMESWARI (The Bioscan, 2010)
A case study was undertaken among individuals residing in a Fluoride affected area. A total of 50 patients of both sexes in the age group of 02- 80 years were selected from a village Thungapeta of Srikakulam district of AP state, where the levels of Fluoride in drinking water varied from 2.9 to 3.5 mg/L. The patients of Dental fluorosis, skeletal fluorosis were examined for Hematological indices and Biochemical evaluation of Creatine kinase and ∝ Amylase. 72% patients are suffering from Aniscocytosis. 64% are suffering from Eosinophilia, 56% from lymphocytopenia. All parameters revealed that fluoride causes hypochromic Anemia. The present study elaborately deals with increased RDW values and suspected heart problems, liver problems and intestinal disorders. The activity of CK, ∝Amylase showed significantly rise and they alter skeletal and hepatic function.